Redesigning retail spaces based on customer habits and halal standards using market basket analysis - Yanti, Roaida; Qurtubi, Qurtubi; Setiawan, Danang; Maradjabessy, Prita Nurkhalisa; Faisol, Nasruddin (International Journal of Advances in Applied Sciences, 2025)
The halal retailing standard was first introduced by the Department of Malaysian Standards in 2010, known as MS 2400-3:2010. This standard was developed to protect Muslim consumers with the assurance of halal products. However, this management system needs to be more prescriptive on how the retail layout should be organized. In addition, this management also overrides the consideration of customer purchase behaviors or preferences. This research aims to design the layout of retail outlets by considering customer buying behavior and halal retailing standards. This study used the association rule-market basket analysis (AR-MBA) to determine the pattern of customer shopping behavior. One Islamic retail in Indonesia was used as a case study, where one-month sales transaction data was analyzed using AR-MBA. In addition, the activity relationship chart (ARC) was used to qualitatively analyze the placement of a product department by considering halal retailing standards. The results of AR-MBA obtained 21 associations among product departments, which were then used as a basis for proposed layouts while still considering the product characteristics and halal retailing standards. This research output provided a proposed product layout for retail outlets by considering quantitative factors (AR-MBA output) and qualitative factors (MS standard).